2017
DOI: 10.1186/s13100-017-0094-z
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of the mariner element galluhop in avian genomes

Abstract: Background: Transposable elements (TEs) are highly abundant genomic parasites in eukaryote genomes. Although several genomes have been screened for TEs, so far very limited information is available regarding avian TEs and their evolutionary histories. Taking advantage of the rich genomic data available for birds, we characterized the evolutionary history of the galluhop element, originally described in Gallus gallus, through the use of several bioinformatic analyses. Results: galluhop homologous sequences were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
1
0
3
Order By: Relevance
“…Анализ геномов разных видов птиц позволил проследить историю внедрения, распространения и эволюции некоторых ДНК-транспозонов (Bertocchi et al 2017;Morris et al 2020), хотя их доля по сравнению с описанными выше элементами в геномах птиц существенно ниже. В геномах птиц не обнаружены другие типы ДНК транспозонов, кроме характеризующихся наличием терминальных инвертированных повторов.…”
Section: организация некодирующих элементов в геномах птицunclassified
See 2 more Smart Citations
“…Анализ геномов разных видов птиц позволил проследить историю внедрения, распространения и эволюции некоторых ДНК-транспозонов (Bertocchi et al 2017;Morris et al 2020), хотя их доля по сравнению с описанными выше элементами в геномах птиц существенно ниже. В геномах птиц не обнаружены другие типы ДНК транспозонов, кроме характеризующихся наличием терминальных инвертированных повторов.…”
Section: организация некодирующих элементов в геномах птицunclassified
“…У домашней курицы в качестве рассеянных повторяющихся элементов наиболее широко представлены два достаточно древних семейства ДНК-транспозонов Charlie12 и Galluhop (Wallis et al 2004;Wicker et al 2005). Последний относится к Mariner-подобным элементам и обнаружен в разном количестве в геномах пяти видов Курообразных: домашней курицы, индейки, японского перепела, виргинской американской куропатки и тетерева-косача, а также у одного из видов птиц-носорогов -малайского калао (Bertocchi et al 2017). Проникновение транспозона Galluhop в геномы представителей обоих групп произошло, по-видимому, путем горизонтального переноса.…”
Section: организация некодирующих элементов в геномах птицunclassified
See 1 more Smart Citation
“…Another recent finding about HTT in birds was the first example of HTT between bird species. Bertocchi et al 2017 reported the first HTT event of mariner gallohop elements between two bird orders: Galliformes and Buceritiformes which diverged around 85–98 Mya [ 39 ].…”
Section: Main Textmentioning
confidence: 99%